(untitled) (Journal of Mechanical Engineering, 2014)
The problem of industries becoming sick in recent years, both in public and private sectors inBangladesh and also in some cases in some other developing and underdeveloped countries, has turned to bealarming. Although the causes for closure or divestment might be many but in most of the cases continued lossplayed a major role in industries becoming sick. Thus the problem of industries becoming sick deserves to betreated more seriously at Government policy level, and also by the researchers in academic and industrialarena, as it is related to the economy and development of a country. Every industry can be seen as a systemworking in diversified environment. It operates under the influence of many external and internal factors.Various combinations of external and internal factors are responsible for industries to becoming sick. But thesetoo vary from country to country, economy-to-economy, etc. It can be said for surely that the causes forindustries becoming sick shall not necessarily be similar in under-developed, developing and developedcountries. In this paper an attempt has been made to identify the causes of industries becoming sick inBangladesh and to show how far the application of the theories and principles of Production and OperationsManagement play a role in the prevention of industries becoming sick. No attempt has been made here todiscuss and even to analyze the causes for industries becoming sick related to industrial policy of the country,legal and other related rules and regulations, industrial competitions, influence of local politics, open marketeconomy, etc. DOI: http://dx.doi.org/10.3329/jme.v43i2.17831